2022
DOI: 10.23887/jere.v6i2.40312
|View full text |Cite
|
Sign up to set email alerts
|

Learning Intensity and Visual Learning Style on Learning Outcomes

Abstract: Learning activities do not have to be done for a long time. Good learning intensity is carried out regularly will make learning activities a habit. The learning process also needs to be supported by a learning style that suits the characteristics of students. This study aimed to analyze the intensity of learning-on-learning outcomes, visual learning styles on learning outcomes, and learning intensity and visual learning styles on learning outcomes. This type of research is quantitative with a descriptive quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…The matter is not limited to learning a language only, as the learner can learn geographical locations, scientific facts, or even scheduling work. [2]: [5] Each age group has requirements. Younger ages prefer drawings, shapes and colours, so this was taken into consideration through the research questions, where the writing is in a small size compared to the pictures, which were larger in size so that the learner can focus on them more than writing.…”
Section: Some Concepts In Educationmentioning
confidence: 99%
“…The matter is not limited to learning a language only, as the learner can learn geographical locations, scientific facts, or even scheduling work. [2]: [5] Each age group has requirements. Younger ages prefer drawings, shapes and colours, so this was taken into consideration through the research questions, where the writing is in a small size compared to the pictures, which were larger in size so that the learner can focus on them more than writing.…”
Section: Some Concepts In Educationmentioning
confidence: 99%
“…This indicates that students are able to learn more about statistics if they have something to look at visually in their lessons. In [22], it is found that most students nowadays are visual learners who easily remember things through shapes, pictures, and other visual representations of the lessons. Likewise, it is also depicted in [10] that the visual learning style is preferred since students are more active and have experienced more engagement in the classroom as opposed to other learning styles.…”
Section: The Learning Style Of Studentsmentioning
confidence: 99%
“…Also, its capability to integrate visual elements, such as diagrams, animations, and images, aids in providing clear and visual representations. This visual support helps students grasp complex ideas and processes more effectively (Muslim et al, 2022;Rezeki & Kamaludin, 2023;Winarti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%